Evaluation of Efficacy of Online Case Based Learning as a Teaching Learning Tool in Undergraduate Oral Pathology Course - Shrestha, Bijayata; Subedi, Sushil; Koirala, Ujjwal; Paudel, Ishwori Sharma; Paudel, Sabita (Birat Journal of Health Sciences, 2021)
Introduction: COVID-19 had enforced educational institutes to adopt online learning.Objectives: This study was designed to compare the learning outcome of online case and online lecture based learning in the undergraduate Oral pathology module of our institute and to compare the perception of students towards the course atiended.Methodology: The 3rd year dental students (N=25) were split into – online case based learning (A1=6, A2=6) and online lecture based learning groups (B=13) randomly. An online multiple choice questions tests were conducted before and after the interventions. An online questionnaire based survey was conducted to evaluate students' perceptions toward the course attended. The statistical analysis was done using paired t test and Mann Whitney U test.Results: Online case based learning was found to be a more effective learning method than online lecture based learning group (online case based learning post test mean rank=16, online lecture based learning post test mean rank=9.54, P=0.026). Significantly more students in the online case based learning group had positive perception towards the course atiended (online lecture based learning; mean value =2.5+/- 0.54, online case based learning; mean value =2.87+/-0.2, P=0.041).Conclusion: Online case based learning should be integrated in Oral Pathology curriculum amidst such pandemics when onsite classes are not possible.